Pengaruh Muhammadiyah terhadap Reformasi dan Modernisme di Indonesia - Nabil Amir, Ahmad; Abdul Rahman, Tasnim (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
This study examines the influence of Kiyai Haji Ahmad Dahlan (1868-1923) in the history of Islamic reform in Indonesia and its impact on modern movements and thought. This study focuses on Muhammadiyah, an Islamic organization founded by Ahmad Dahlan on November 18, 1912, in the context of religious reform and purification. The main objective of this study is to reveal the philosophy and struggle brought by Ahmad Dahlan, a pioneer of modern awareness and awakening in Indonesia. The method used is descriptive-historical with a qualitative approach, combining scientific and empirical reviews. The study results indicate that Ahmad Dahlan's thoughts have greatly influenced the aspirations of modern Islam through Muhammadiyah, which created a broad network of activists and preachers. His contribution to developing rational streams and awareness from the traditions of madhhab and puritanism is very significant. Recommendations include the need for further research on Ahmad Dahlan's influence in a global context and the adjustment of traditional values ​​in contemporary Islamic education to increase the relevance of education in the modern era.